Development of an ion shower system for surface modification of polymer materials - Aceremo, Ma Aisa M. (2007)
Today's demand for new and better products increases the need for research on new fabrication methods. Ion surface modification is one strategy to create new products and enhance already existing materials. Surfaces of materials can be altered and specific properties enhanced by the application of specific ion energies. Ion surface modification is a controllable, clean, dry and robust method that uses inert gases at low cost making it viable for commercialization. It is being used in the microelectronics industry today. Ion bombardment is one method that remains relatively unexplored due to its equipment requirement. A laboratory scale alternative to the expensive commercial ion implanter is the ion shower. The results of this study demonstrate that the ion shower that was originally designed for ion implantation can be retrofitted and developed into a surface modification system for polymer materials like polyethylene using Argon plasma. Benchmarking and qualification procedures performed in initial runs to assess the quality of the plasma showed that the base pressure achievable by the system with a turbo-molecular pump is 2.1 x 10-6 Torr. Since low pressure is necessary to gain the most efficient conversion of energy to electron energy for ionization and for plasma treatment of polymers, Paschen curves specific for Argon were generated from the ion surface modification system from which the minimum breakdown voltage at which stable Argon plasma can be generated was determined at 21 Volts at a minimum pressure of 7.30x10-3 Torr. Using this determined minimum pressure and based on the plasma stability runs, the base pressure employed in the surface modification was set at 10-4 Torr, a pressure achievable using a single evacuation step with a rotary pump. From the beam characterization it was determined that both current density and ion energy of the generated plasma of the ion surface modification system can be controlled by varying the Argon gas filling pressure such that with the appropriate tuning of the current sources (filament, anode, electrostatic lenses, accelerator and solenoid), current density increases as Argon gas filling pressure is increased and ion energies in the low ion energy range can be produced. The results demonstrated that the Argon ion energies at specific exposure times can modify the polyethylene surfaces of both industrial and pure polyethylene. The investigated Argon ion energies were not sufficient to effect chemical modification as was observed on the infra red absorbance spectra of both untreated and treated polyethylene samples. Pressure effects were observed on selected treated samples of the industrial and pure polyethylene. Vibrational analysis show that all of the polyethylene samples, except for two treated industrial polyethylene samples, have higher (more ) amorphous than crystalline content. Both exposure time and argon gas filling pressure showed apparent significant positive (hydrophobic) effect on the treated pure polyethylene. Consideration of the stability of effects on contact angle over time, based on a comparison of changes in estimated effects due to time delays in measurement of the contact angle of Argon plasma treated polyethylene samples, appeared to indicate that as the plasma treated sample was aged, the observed increase in hydrophilicity actually decreased with time. It is most likely that this increase of contact angle with aging time after plasma treatment is due to absorbance of ambient oxygen of the surface already treated with Argon plasma. Correlation of roughness and wettability effects, using the industrial polyethylene data, seem to indicate that increasing roughness will increase the contact angle. Comparison of the micro-features observed on the AFM images of the untreated and treated industrial polyethylene samples appeared to show decrease in the roughness and increase in homogeneity of the surface topography after treatment. The machine settings and procedures determined from this study are essential to benchmark the retrofitted ion shower as a surface modification system and to serve as a protocol for future investigations and continuation of the development of the ion shower as a surface modification system for polymers.
Thesis (M.S. Materials Science and Engineering)--University of the Philippines, Diliman.
Keywords: Ion bombardment; Polymers -- Surfaces; Polyethylene; Plasma polymerization; Surfaces (Technology).